Etika Sosial terhadap Difabel Netra: Analisis Semantik Alquran - Muttaqin, Ahmad (INKLUSI, 2019)
The Qur'an is always positioned as the main source of social ethics in Islam. The problem is, there are several verses of the Quran that describe non-believers (infidels) as blind people. Such a way makes it as if the Quran marginalizes people with disabilities. Therefore, it is important to understand how the actual existence of the blind in a full context of the Quranic view. This paper uses a semantic approach in analyzing the word al-a‘mā and its various derivatives in the Quran. This study concludes: First, the Quran uses al-a‘mā more in a metaphoric meaning; not the blind of the eye, but the blind of the heart. Second, the Quran gives more appreciation to the people with disabilities and at the same time, it criticizes unbelievers during the Prophet's time. [Alquran selalu diposisikan sebagai sumber utama etika sosial dalam Islam. Masalahnya, ada beberapa ayat Alquran yang menggambarkan orang yang tidak beriman (kafir) sebagai orang buta (difabel netra). Cara demikian membuat seolah-olah Alquran memarginalkan mereka. Oleh karena itu, penting untuk memahami bagaimana sebenarnya eksistensi difabel netra dalam bingkai kesatuan wawasan Alquran. Tulisan ini menggunakan pendekatan semantik dalam menganalisis kata al-a‘mā dan berbagai derivasinya dalam Alquran. Penelitian ini menyimpulkan: Pertama, Alquran lebih banyak menggunakan al-a‘mā bukan secara fisik, tetapi tertutupnya hati. Kedua, Alquran memberikan penghargaan lebih kepada difabel netra dan pada saat yang sama Alquran melakukan kritik sosial terhadap orang-orang tidak beriman pada masa Nabi.]